2019
DOI: 10.1080/20445911.2019.1585435
|View full text |Cite
|
Sign up to set email alerts
|

Searching for a word in Chinese text: insights from eye movement behaviour

Abstract: Locating relevant information in text is an important aspect of the reading process, however relatively few studies have examined this, especially for logographic languages such as Chinese. The present study examines eye movement behaviour during search for a target word in Chinese sentences, compared with reading the sentences for comprehension. Although there were clear effects of word frequency during reading for comprehension, the study shows no evidence for an influence of the word frequency of non-target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 60 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…In the semantic acceptability task emphasis was placed on semantic comprehension, and semantic analysis also appeared to occur relatively automatically for the meaningful auditory distractor stimuli, resulting in processing interference. In contrast, participants processed the meaning of the sentences to a much lesser degree in the noncharacter detection task (Rayner & Fischer, 1996; Rayner & Raney, 1996; Wang et al, 2019), and consequently the automatic analysis of speech meaning had little influence on the detection of nonwords (i.e., there was far less shared processing interference).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the semantic acceptability task emphasis was placed on semantic comprehension, and semantic analysis also appeared to occur relatively automatically for the meaningful auditory distractor stimuli, resulting in processing interference. In contrast, participants processed the meaning of the sentences to a much lesser degree in the noncharacter detection task (Rayner & Fischer, 1996; Rayner & Raney, 1996; Wang et al, 2019), and consequently the automatic analysis of speech meaning had little influence on the detection of nonwords (i.e., there was far less shared processing interference).…”
Section: Discussionmentioning
confidence: 99%
“…During natural reading, very robust word frequency effects have been repeatedly demonstrated such that high-frequency words typically receive fewer and shorter fixations than low frequency words. Importantly, however, under conditions of visual search in text, frequency effects on target words (i.e., search targets) are attenuated (e.g., Rayner & Fischer, 1996; Rayner & Raney, 1996; Wang, Sui, & White, 2019). Because the word frequency effect is generally taken as a hallmark of normal word identification (Inhoff & Rayner, 1986; Paterson & Jordan, 2010; Sereno & Rayner, 2003), its absence for the visual search suggests that the extent to which target words are lexically processed is reduced, and such a finding would be entirely consistent with the claim that during visual search readers process text for meaning to a lesser degree than they do when they are reading to form a semantic judgment.…”
Section: Interference-by-processmentioning
confidence: 99%
“…In such a situation, forward saccades are longer and fixations shorter. In addition, fixation durations are much less influenced by the frequencies of the words (Rayner & Fischer, 1996;Wang, Sui, & White, 2019). Reichle, Pollatsek, and Rayner (2012) argued that this pattern of eye movements can be understood by assuming that words are no longer processed for meaning but for form (based on a coarse familiarity check).…”
Section: Normal Silent Reading Rate In English Is 238 Wpm For Non-ficmentioning
confidence: 99%
“…Similar results were reported by Rayner and Fischer (1996), where they showed that word frequency affected fixation durations in normal reading but did not affect fixation durations when the task required searching for a target word in normal text. A more recent study conducted in the context of Chinese reading also reported a lack of word frequency effects in a task where participants were required to search for a specific target within Chinese texts (Wang et al, 2019). Thus, it has been argued that eye-movement control operates according to quite different principles during normal reading and visual search, such that the determinants of when to move the eyes vary as a function of task demands (Rayner, 1995;Rayner & Fischer, 1996;Rayner & Raney, 1996; see also Vitu et al, 1995, for a different view).…”
Section: Introductionmentioning
confidence: 99%
“…One motivation of the current study was to better understand what is driving frequency effects in target search during the scanning of normal text, and Landolt-C strings (Rayner & Fischer, 1996;Rayner & Raney, 1996;Vanyukov et al, 2012;Wang et al, 2019). According to processing models of eyemovement control, the trigger of when to move the eyes differs across visual search and reading in that these two tasks impose different cognitive processing demands (Rayner, 1995;Rayner & Raney, 1996;Reichle et al, 2008;Reichle et al, 2012).…”
Section: Introductionmentioning
confidence: 99%